The Irish Novel 1800-1910 - O'Brien, George, 1945- (Book collections on Project MUSE., 2016)
This wide-ranging book surveys the landscape of the Irish novel from the Act of Union to the end of the Edwardian era. Thirty representative works are selected for fluent and accessible discussion. Focusing on the problematic condition of the protagonist, each discussion combines close reading with considerations of such broader thematic and conceptual issues as identities, contexts, genres and language. An insightful introduction underlines these issues' significance, and a further understanding of that is provided by noting their various iterations over the whole range of novels selected. Discussion of each individual work is prefaced by a biographical and critical overview of its authors. The work's originality and diversity is further enriched by its reconfiguration of the nineteenth-century Irish novel's canon. Neglected works are critically assessed, some for the first time. Fictional views of Ireland by English writers including Thackeray and Trollope are evaluated, a departure which also opens up new lines of inquiry into nineteenth-century Anglo-Irish literary relations. The relevance to Irish literary culture of works with English settings by expatriate Irish writers such as Charlotte Riddell, George Moore, Bernard Shaw, Oscar Wilde and Bram Stoker is also critically explored.